Remote Phonon Control of Quantum Dots and Other Artificial Atoms. Issue 4 (12th March 2021) - Wigger, Daniel; Gawarecki, Krzysztof; Machnikowski, Paweł
Abstract: To exploit the full potential of chips for quantum technologies, it is worth considering all possible opportunities offered by the solid state. The aspect covered in this article is the use of phononic fields to remotely influence the optical properties of artificial atoms. The three most commonly used strain sources are discussed, that is, mechanical resonators, surface acoustic waves, and picosecond acoustic pulses. All three platforms are routinely interfaced with quantum dots and other qubits in basic research, which renders a first step toward large scale implementation in quantum applications. A central question regarding the interaction between lattice oscillations and the optically active artificial atoms deals with the characteristic time scales of the two components. The influence of this aspect on the expected optical response on the phononic driving is discussed. Besides well known semiconducting quantum dots and color centers that typically operate in the visible spectral range, the more recently discovered artificial atoms in layered van der Waals materials are discussed. Due to their flexibility and robustness, these crystals promise vast opportunities for future applications. Another important building block lies in superconducting qubits that allow to resonantly generate quantum phonon states and therefore establish the field of quantum acoustics. Abstract : It is discussed how phonons can be used to remotely and dynamically manipulate the optical properties of quantum dots and other artificial atoms. The presented phonon sources are mechanical resonators, surface acoustic waves (SAWs), and picosecond acoustics. The interplay between SAWs and superconducting systems is also discussed and a short perspective on artificial atoms in van der Waals materials is given.